Divulgação Científica de Astronomia no Jornal Diário de Belém entre os anos de 1881 e 1884 - CALDAS, Jocasta (2021)
The historical construction of scientific dissemination is an important step in the analysis and improvement of the techniques of dissemination and popularization of science carried out today. Despite its recent history in Brazil, and even more recently in the Brazilian Amazon region, understanding the initial development of scientific communication in the country helps to better train future professionals in the area. With the intention of rescuing the memories about the beginning of the Brazilian scientific dissemination, we conducted research on the astronomy theme in Amazonian newspapers of the second half of the 19th century. In this work, we deal with the astronomical dissemination that was carried out in the State of Pará, specifically in the newspaper "Diário de Belém", with emphasis on the column initially entitled Sciencias, which included information about planets, comets, astronomical instruments, as well as translations of works from the scientific literature of the late nineteenth century.